The Existence of Digital Literary Criticism and Its Contributions in Preparing Literary Criticism Teaching Materials Post Covid 19 Pandemic - Dewa Gede Bambang Erawan; Putu Devi Maharani; Ni Wayan Suastini; Ida Ayu Made Wedasuwari; Luh Putri Pramesti Artayani; I Komang Asmara Utama (Journal of Education Reseach and Evaluation, 2024)
Literary criticism teaching materials provided on campus only focus on theory and very few opportunities to appreciate literary texts directly through reading and understanding literary criticism published in various sources. Learning literary appreciation, including literary criticism, should not only be about memorizing literary theories, but also through practices such as reading and enjoying literary works directly, as well as appreciating the literary works read. The purpose of this research is to analyze the existence and contribution of digital literary criticism in the preparation of teaching materials for literary criticism. The design used in this research is qualitative. The data analysis technique used is descriptive qualitative through data triangulation. The results of this study show that in the span of one year the average number of literary criticism published in digital media. The data shows that digital literary criticism still exists to provide color in the literary treasury regardless of the dynamics of the ups and downs of the number of literary criticisms published through digital media. Based on the information obtained through the distribution of questionnaires, it is known to contribute to the preparation of teaching materials for literary criticism. Regarding students' interest in digital literary criticism in literary criticism teaching materials, they successfully received a response with a high category. In conclusion, digital literary criticism enriches and expands the scope of teaching materials for literary criticism, making it more dynamic and adaptive to the latest developments in the world of literature and education.